Analysis of Management Functions in an Efforts to Improve the Efficiency and Effectiveness of Management of Medicines and Expiry Medical Materials: JEL Classification: I10, I18, M11, M12, H83 - Osse Lembang; Andi Nur Insan; M.Nasir Hamzah (Journal La Bisecoman, 2025)
This study aims to analyze the application of management functions in the management of drugs and medical consumables (BMHP) to enhance efficiency and effectiveness at the Regional General Hospital (RSUD) of Nunukan Regency. The research focuses on the four key management functions: planning, organizing, actuating (implementation), and controlling (supervision), while also identifying the challenges and implications of BMHP logistics management for healthcare service quality. Using a qualitative research approach, data were collected through in-depth interviews, direct observation, and document analysis. Informants included hospital leaders, pharmacy installation heads, pharmacists, logistics staff, and patients. The results show that the planning function is carried out based on consumption methods and VEN (Vital, Essential, Non-Essential) and ABC analysis, but still lacks support from an integrated information system. The organizational structure exists, but its implementation is not yet optimal. The implementation function follows SOPs, although constrained by billing system issues and geographical challenges. Supervision is conducted both internally and externally, but regular monitoring is still limited. Key obstacles include budget constraints, payment delays, and logistics challenges due to the hospital's remote border location. Efficient and effective management has a direct impact on the quality of patient services, particularly in drug availability, service timeliness, and patient satisfaction. This research recommends improving logistics information systems, strengthening interdepartmental coordination, adjusting budgeting strategies, and increasing accountability to ensure high-quality pharmaceutical governance in regional public hospitals.